TANGGUNG JAWAB ORANG TUA UNTUK MEMPERSIAPKAN GENERASI TANGGUH DALAM PERSPEKTIF AL-QUR’AN ANALISIS SEMANTIK TERHADAP Q.S. AL-NISA’: 9 - Muthi’ah Hijriyati; Ali Said (EL-Islam, 2019)
Being a parent has the logical consequence of responsibility for children. The task of parents is not as simple as only growing and fulfilling children's clothing, shelter and food but also responsible for all aspects of a child's life in the world to the hereafter. Al-Qur'an itself also regulates it in its various verses (ayat), either in the form of a direct word or in stories that can be learned. As QS al-Nisa ' verses (ayat) nine emphasizes the obligation of parents to prepareeverything as much as possible for their offspring‟s future, especially if parents cannot accompany children to adulthood. The threat of not leaving their children in a weak condition is mentioned twice with different stressing since in Al Qur'an, there is no word that is truly synonymous even if it is interpreted in Indonesian with the same meaning. Therefore, this verse is understood as the duty and responsibility of parents to prepare themselves and focuson making a strong generation